Impact of seasons and wastewater cultivation on the biomass and biodiesel production by the Plectonema terebrans BERC10 as a candidate for a multiproduct algal biorefinery. (15th January 2023) - Haider, Muhammad Nabeel; Khan, Aqib Zafar; Usman, Muhammad; Balakrishnan, Deepanraj; Javed, Muhammad Rizwan; Malik, Sana; Liu, Chen-Guang; Mehmood, Muhammad Aamer; Ashraf, Ghulam Abbas
Highlights: A newly isolated filamentous cyanobacterium was studied in outdoor cultivation system. Seasons-based variation in abiotic factors affected the metabolite biosynthesis. Summer conditions improved the biomass and biodiesel production. Strain has shown a contamination-free cultivation in open pond system. The strain demonstrated the promising potential for urban wastewater treatment. Abstract: Cyanobacteria offer efficient resource recovery and biotransformation of the wastewater-derived nutrients into valuable bioproducts. However, to achieve commercial robustness, the cultivation potential of the strain must be evaluated under outdoor conditions. The present study evaluated the potential of a filamentous cyanobacterium Plectonema terebrans BERC10 for resource recovery, wastewater treatment, and biomass production for the whole year using an outdoor open-pond cultivation system. The seasonal and nutrient variations had a strong impact on metabolites and biomass production. Accordingly, the maximum biomass production of 1.9 g/L was produced during the summer season (34–42 °C) while 1.7 g/L, 1.554 g/L, and 1.526 g/L biomass was produced during spring, fall, and winter, respectively. The strain adjusted the pH of the wastewater from 7.5 to 11, offering contamination-free cultivation with easier floatation-based harvesting due to its filamentous nature. Besides, wastewater-based outdoor cultivation diverted the metabolic fluxes towards lipid biosynthesis where it accumulated 50–63 % lipids throughout the year. In addition, a maximum of 21 % carbohydrate content was observed during the summer season, while 9.2 %, 13.11 %, and 17 % were measured in the winter, spring, and fall seasons, respectively. The 16–27 % protein content was achieved throughout the year which was shown to be correlated with the varying nitrogen concentration during different seasons. The biomass produced during all four seasons was separately subjected to cascading processing to make the process cost-effective, and 60 % lipids and 25 % proteins were recovered while the residual biomass contained fermentable carbohydrates. Moreover, the strain showed a promising wastewater treatment potential by lowering the total nitrogen by 90 %, total phosphorus by 99 %, total dissolved solids by 70 %, COD by 80 %, and BOD by 85 %. In conclusion, it exhibited remarkable adaptability to the fluctuating environmental conditions, wastewater treatment, and biodiesel production. Further upscaling and techno-economic analyses are the prospects of the study.